Analysis of optical vortices interaction using computer generated holograms - Lin, Jiao. (2008)
A program developed in the Matlab environment which can generate arbitrary shape of vortex is presented. Another application of CGH is shown that moire fringes produced by superposition of CGHs can be used to analyze the interference of optical vortices.